Impacts of Short Message Service Texting on University Students in Malaysia - Andrew, Yau-hau Tse (2012)
Short Message Service (SMS) texting is widely used in this technological era, which has led to the questioning of the social and psychological effects of this communication medium. The objective of this study is to investigate the social and psychological influence on using SMS texts among university students in Malaysia. A sample of 971 respondents completed the online questionnaire. The findings indicated that there was a clear distinction between ‘Texters’ and ‘Talkers’ in the way they use their mobile phones and their underlying incentives. The key finding in the analysis was that Texters tend to form close ‘text circles’ with their own social ecology, interlinking with a close group of friends. Compared to Talkers, Texters were found to be more lonely and socially anxious, and likely to unveil their ‘real-self’ through text than voice communication. To conclude, people use their phones differently because they have different personalities and needs.